Temperature effects on DLC coated micro moulds - Andrew Rees (Surface and Coatings Technology, 2016)
Microinjection moulding is a key enabling technology for replicating miniaturized components and parts with functional features at the micrometer and even sub-micrometer length scale. The micro moulding tools used in the process chain are critical for delivering high quality parts for the duration of the product life cycle, and recently tool coatings such as Diamond-like carbon (DLC) have been used to extend their use and enhance the performance. The micro injection moulding process has high injection speeds with cyclic heat transfer characteristics, and little is understood on how the localised heat transfer at the surface will influence the DLC surface coating delamination and cracking. In this research a microinjection moulding process using three different polymers, Polypropylene (PP), Acrylonitrile butadiene styrene (ABS) and Polyether ether ketone (PEEK) is studied. Finite element analysis (FEA) simulation is utilised to identify the process temperature factors that lead to tool thermal expansion and dimensional changes that directly impact the life cycle of the coating. The theoretical and FEA results show that the mould material and the two coatings experience a significantly different thermal expansion from each other. It has also been shown that at the micro scale heat loss at the tool surface is dominant, and the variation in heat has a significant influence on the different thermal expansion rates. In particular the DLC coated micro rib features are particularly susceptible to high variations in heat transfer. The research identifies areas of the tool surface that experience sudden heat variation across the part surface, and concludes that through process optimisation it is possible to reduce the potential for DLC coating delamination and cracking during service.